Arterial involvement of lower limbs in peripheral artery disease - the difference between diabetics and non-diabetics - Tanzeela Khan; Naheed Khan; Sajida Qureshi (Journal of the Pakistan Medical Association)
Objective: To detect peripheral artery disease in diabetic and non-diabetic individuals.